Variables of the physique in young basketball player girls - Farkas, A.; Bosnyák, E.; Szmodis, M. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: In the area of female sport it is an interesting and exciting topic, to investigate the differences of the bodily development level of matured and unmatured girls. In our sample the differences of the body parameters, if any, in a group of young basketball player girls, from Sopron, in Hungary were studied.